Effects of Sevoflurane Inhalation Anesthesia on the Intestinal Microbiome in Mice - Han, Ci; Zhang, Zhaodi; Guo, Nana; Li, Xueting; Yang, Mengyuan; Peng, Yahui; Ma, Xiaohui; Yu, Kaijiang; Wang, Changsong (Frontiers in Cellular and Infection Microbiology, 2021)
In recent years, more and more attention has been paid to intestinal microbiome. Almost all operations will go through the anesthesia process, but it is not clear whether the intervention of anesthesia alone will affect the change in the intestinal microbiome. The purpose of this study was to verify the effect of sevoflurane inhalation anesthesia on the intestinal microbiome. The animal in the experimental group was used to provide sevoflurane inhalation anesthesia for 4 hours. The control group was not intervene. The feces of the experimental group and the control group were collected on the 1st, 3rd, 7th and 14th days after anesthesia. Sevoflurane inhalation anesthesia will cause changes in the intestinal microbiome of mice. It appears on the 1st day after anesthesia and is most obvious on the 7th day. The specific manifestation is that the abundance of microbiome and the diversity of the microbiome is reduced. Subsequently, the intestinal microbiome diversity of mice showed a trend of recovery on the 14th day. However, the abundance of differential bacteria did not recover with the changing trend of diversity. Sevoflurane inhalation anesthesia is associated with changes in the intestinal microbiome, and these changes can last for at least 14 days.